Impact of Cotton IPM Program on Profitability, Human Capital and Environment in Southeastern Region of Bangladesh - Islam, SMF; Khan, MI; Islam, MS (Progressive Agriculture, 2014)
Present study examined the socio-economic impacts of cotton IPM program of Food and Agricultural Organization (FAO) on yield, farmers income, health, environment and human resources development in selected areas in the southwestern region of Bangladesh. Ninety nine respondents were randomly selected by using two- stage stratified sampling technique. Farmers were stratified as farmers Field School (FFS), Non Farmers Field School (Non-FFS) and Non-IPM groups. Data were collected through two surveys i) baseline survey and ii) impact assessment survey. It was found that cotton IPM program has significant impact on uses of fertilizers, pesticides, yield, environment, bio-diversity and farmers knowledge of management of bio-resources and environment. The FFS farmers reduced fertilizers by 58% and pesticides by 62% compared to baseline situation. The FFS farmers reduced variable cost of production by 30%. However, cotton yield was less compared to base year due to unfavorable rainfall in the cotton field in 2004. Higher level of employment opportunities was created in different categories of farmers FFS (40 %), Non-FFS (28%) and Non-IPM (8%) after the participation in the cotton IPM program. Environmental Impact Quotient (EIQ) shows an improvement of 46% on FFS farms as compared to only 2% improvements caused at Non IPM farms. The cumulative score on soil improvement, observed biodiversity and attitude towards environment had significantly improvement on FFS farms (160%). Use of sources of information had increased (29%) at FFS farms and declined at other categories. The major changes were found in the recognition of number of beneficial pests of FFS farms. The observation and record keeping skill of farmers for participatory field experiments were found to increase for the FFS farms after participation in IPM program. DOI: http://dx.doi.org/10.3329/pa.v18i2.18279 Progress. Agric. 18(2): 255 - 269, 2007